THE ABBREVIATION WAKAMONO KOTOBA AT COMIC “GALS!” VOLUME 1 - OCTORA, GARDIOLA AYU (Jurnal Ilmiah Mahasiswa FIB, 2013)
ABSTRACT Wakamonokotobais the language usedbyyoung Japaneseto communicatewithfriends. One characteristic ofwakamonokotobaisabbreviation. The function of abbreviation is tofacilitate thepronunciationof long words, confidentiality, and strengthen the sense ofsolidarity. Thisstudyis using thequalitativedescriptive. The data source iscomic entitledGals! volume 1. This comiccontainingwakamonokotoba’s expressions for experiencingthe abbreviation.The analysisperformed usingtheidentification of wakamonokotoba’sabbreviation, according totheabbreviationtabulationanddescription of the results. The results showedthat (1)from 35wakamonokotobaexperiencingabbreviation, 17 wordsclassifiedtanshikishouryaku, 11 wordsclassifiedfukushikishouryakuand8 wordsforman exception, (2)on tanshiki shouryakuwere found jouryaku, chuuryaku, geryaku, (3) on fukushiki shouryaku were found, fukushiki shouryaku, a compound word made ​​up of two and three words combined, (4) while the form of exemptions, there are 3 patterns were identified, namely toujigo, the samewordhas twodistinctforms ofshort word,with adifferentformationsbefore. The authorssuggestfor the further researchon the topicwakamonokotobaterms ofwritingoranalysisconstrastivesakasakotobaJapaneselanguagemisfortune. Alsoit is recommendedto usethe Japanese nativesourceswho has the ability of the real production in the Japanese language. Key words :abbreviation, morphology, wakamono kotoba